3D Surface Reconstruction of Plant Seeds by Volume Carving: Performance and Accuracies - Roussel, Johanna; Geiger, Felix; Fischbach, Andreas; Jahnke, Siegfried; Scharr, Hanno (Frontiers in Plant Science, 2016)
We describe a method for 3D reconstruction of plant seed surfaces, focusing on small seeds with diameters as small as 200 µm. The method considers robotized systems allowing single seed handling in order to rotate a single seed in front of a camera. Even though such systems feature high position repeatability, at sub-millimeter object scales, camera pose variations have to be compensated. We do this by robustly estimating the tool center point from each acquired image. 3D reconstruction can then be performed by a simple shape-from-silhouette approach. In experiments we investigate runtimes, theoretically achievable accuracy, experimentally achieved accuracy, and show as a proof of principle that the proposed method is well sufficient for 3D seed phenotyping purposes.